Public procurement can hinder innovation - Bastian Krieger; Malte Pruefer; Linus Strecke (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Public procurement accounts for 15 to 20 percent of global GDP and is considered an effective innovation policy. However, the detrimental effects of non-innovative public procurement - public procurement tenders awarded solely based on their price - on firm innovations have been largely neglected, even though it represents the majority of all tenders. We contribute by i) developing a comprehensive theory on the effects of winning non-innovative public procurement tenders as a firm and ii) empirically testing our theory by combining representative German data with two-way fixed effect difference-in-differences estimations. In total, the estimations demonstrate winning non-innovative public procurement reduces firms' product and process innovations on the one hand, and increases firms' focus on their established products and services on the other hand. These results confirm our theory and empirically hold at the level of the individual firm and the German enterprise sector.
Keywords: O31; O32; O38; H57; 330; Public procurement; Firm innovation; Demand side